Elastic, mechanical and thermodynamic properties of zinc blende III-X (X= As, Sb): ab-initio calculations - IBRIR, Miloud; HADJAB, Moufdi; BATTAL, Gazi Yalcin; BOUZID, Fayçal; HADJ LARBI, Abderrahim; BOUDOUR, Samah; NEZZARI, Hassene (جامعة الوادي - university of el oued, 2019)
In this work, density functional theory plane-wave full potential method, with local density approximation (LDA) are used to investigate the structural, mechanical and thermodynamic properties of of zincblende III-X ( X= As, Sb) compends. Comparison of the calculated equilibrium lattice constants and experimental data shows very good agreement. The elastic constants were determined from a linear fit of the calculated stress-strain function according to Hooke’s law. From the elastic constants, the bulk modulus B, shear modulus G, Young’s modulus E, Poisson’s ratio σ, anisotropy factor A, the ratio B/G and the hardness parameter H for zincblende III-X ( X= As, Sb) compound are obtained. Our calculated elastic constants indicate that the ground state structure of III-X ( X= As, Sb) is mechanically stable. The sound velocities and Debye temperature are also predicted from elastic constants
Article
Keywords: Mechanics, Mechanics, energy, DFT, LDA